A Case of Response to Immunotherapy in a Patient With MSI Metastatic Colorectal Cancer and Autoimmune Disease Receiving Steroid Therapy. Issue 5 (June 2020) - Massucci, Maria; Di Fabio, Francesca; Rojas Llimpe, Fabiola L.; Ardizzoni, Andrea
Abstract : Colorectal cancer is one of the most commonly diagnosed tumors worldwide and a leading cause of cancer-related death. Although the majority of gastrointestinal cancers are generally considered poorly immunogenic, recent data from clinical trials have demonstrated that the subgroup of patients with DNA mismatch repair system is highly responsive to immune checkpoint inhibitor–based therapy. We present the case of a 74-year-old man with pulmonary autoimmune intersitiopathy and microsatellite instability metastatic colorectal cancer who responded to nivolumab despite the concomitant steroid therapy. Furthermore, his autoimmune disease did not worsen during immunotherapy.